The Fruit Flies (Diptera, Tephritidae) in Tehran Province, with New Records for Iranian Fauna - Mohamadzade Namin, S.; Nozari, J.; Rasoulian, Gh. (Вестник зоологии, 2010)
As the result of studies of the tephritid flies in Tehran Province (Iran) in 2008–2009, 38 species of 22 genera are found to occur in this region; altogether 47 species are listed; of them, 9 species and 2 genera (Chetostoma and Xyphosia) are recorded for the first time for Iranian fauna. In addition, Steptorrhamphus tuberosus is reported as a new host plant for Ensina sonchi.